he Experience of Combating Corruption in South Korea and Singapore - A. M. Shunaev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article explores the system of measures to counteract the corruption threat in South Korea and Singapore. The relevance of this topic is due to the need to apply in the Russian Federation the best practices of developed countries that successfully apply anti-corruption mechanisms. The author examines the legislative features of neutralizing the corruption threat, analyzes the data on corruption-related crimes identified and investigated. The study takes into account the historical aspect of counteracting corruption, the specific functioning of specialized organizations (ACRC in South Korea and CPIB in Singapore) that implement the full range of anti-corruption activities.